Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/hbm.26056
|View full text |Cite|
|
Sign up to set email alerts
|

Brain‐wide versus genome‐wide vulnerability biomarkers for severe mental illnesses

Abstract: Severe mental illnesses (SMI), including major depressive (MDD), bipolar (BD), and schizophrenia spectrum (SSD) disorders have multifactorial risk factors and capturing their complex etiopathophysiology in an individual remains challenging. Regional vulnerability index (RVI) was used to measure individual's brain‐wide similarity to the expected SMI patterns derived from meta‐analytical studies. It is analogous to polygenic risk scores (PRS) that measure individual's similarity to genome‐wide patterns in SMI. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 81 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…Large-scale neuroimaging studies in SMIs performed by the ENIGMA consortium have led to the discovery that regional brain deficit patterns associated with SMIs are persistent, stable, replicable across ethnically diverse populations, and associated with clinical and cognitive features in SMI patients ( Kochunov et al, 2020a ). The RVI was developed as an analog of PRS to translate these patterns to the individual level and has demonstrated sensitivity and specificity for illnesses, association with cognitive deficits in patients, and ability to predict treatment resistance (Kochunov et al, 2021c , 2020b , 2019 ). Higher SMI PRS is associated with poorer cognition and mental health in non-psychiatric populations ( Liebers et al, 2016 ; Shen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale neuroimaging studies in SMIs performed by the ENIGMA consortium have led to the discovery that regional brain deficit patterns associated with SMIs are persistent, stable, replicable across ethnically diverse populations, and associated with clinical and cognitive features in SMI patients ( Kochunov et al, 2020a ). The RVI was developed as an analog of PRS to translate these patterns to the individual level and has demonstrated sensitivity and specificity for illnesses, association with cognitive deficits in patients, and ability to predict treatment resistance (Kochunov et al, 2021c , 2020b , 2019 ). Higher SMI PRS is associated with poorer cognition and mental health in non-psychiatric populations ( Liebers et al, 2016 ; Shen et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The RVI outperformed any single regional brain measure in explaining symptom severity, illness duration, and cognitive deficits in patients with SMIs ( Kochunov et al, 2019 , 2020a , 2021c ). Sensitivity, specificity, and association with cognition were on par with or exceeded that of PRS in patients ( Kochunov et al, 2021b ). Moreover, the RVI for SSD explained variance in cognitive performance among healthy controls, suggesting that the RVI may be applicable to the general population and capture the continuum of subclinical and clinical variation ( Kochunov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 88%
“…Distinctly methylated genes seem to impact DNAm on phenotype differences, such as susceptibility to certain diseases and pathogens and response to drugs and environmental agents [ 80 ]. Many genome-wide association studies have provided a growing list of genetic variations associated with psychiatric phenotypes and have clarified the shared and unique components of mental illness [ 81 , 82 , 83 ]. A genome-wide meta-analysis study analyzing eight psychiatric disorders has found 146 risk loci, of which 109 are associated with at least two psychiatric disorders, confirming the effect of genetic risk variants and highlighting the close genetic relationship between some diseases, such as schizophrenia and bipolar disorder [ 84 ].…”
Section: Regulation Of Dnam By Cbdmentioning
confidence: 99%
“…Regional brain deficit patterns show both similarities and unique features when compared across mental illnesses (Kochunov, Hong, et al, 2020 ). Recently, we showed that an individual brain's similarity to the overall representative pattern of a specific brain illness may serve as a phenotype more sensitive and specific in predicting disease severity than the disease effect on any individual brain structures (Kochunov et al, 2022 ). Here we develop an individual similarity index for MET and use it to study whether effects of MET have contributed to imaging results in mental illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies found that higher RVI for SSD was correlated with poorer treatment response and greater negative symptoms in patients, as well as decreased processing speed in controls (Kochunov, Huang, et al, 2019 ). Alzheimer's disease (AD) RVI measures also revealed similarities between brain abnormalities in SSD and AD (Kochunov, Zavaliangos‐Petropulu, et al, 2021 ), but this index was not significantly elevated in patients with MDD or BD and vice versa (Kochunov et al, 2022 ; Kochunov, Ryan, et al, 2021 ) suggesting RVI also offers some disease specificity. The direct testing of RVI versus a similar index derived from genetic effect sizes—the polygenic risk score (PRS)—showed that RVI had greater specificity and stronger effect sizes for case–control differences than the PRS, further supporting the validity of the RVI construct (Kochunov et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%